Probing Hippocampal Activity in Sleep, Sleep Deprivation, and Recovery Sleep - (:unkn) unknown (My University, 2022)
Long-term memories are established over several hours of sleep following their initial acquisition. Large-scale recordings from the hippocampus have revealed that neurons reactivate or `replay' wake-induced activity in subsequent sleep episodes, leading many to suggest replay as an underlying mechanism for sleep-mediated memory consolidation. In this dissertation, I describe experiments that examine the extent of hippocampal replay during sleep and how replay is affected in the absence of sleep. In Chapter 2, we found that the hippocampus reactivates neuronal patterns expressed during exploration of a novel environment for upto 10 hours in subsequent sleep with a half-maximum timescale of $~$6 h and is much longer than previously reported durations for hippocampal reactivation. On the contrary, reactivation lasted for less than 30 minutes after exploration of familiar environments. In Chapter 3, we carried out long-duration electrophysiology recordings to investigate how the hippocampal replay is affected when animals are subjected to prolonged wakefulness instead of sleep. We sleep deprived animals for 5 h following exploration of a novel environment, after which the animals were left undisturbed for $~$4 h to recover from extended waking. We observed that, compared to normal sleep, neuronal firing rates and the rate of sharp wave-ripples increased during sleep deprivation, indicating altered dynamics of the hippocampal network. Despite enhanced network activity, we found that the hippocampal replay was severely attenuated by sleep loss. Interestingly, we observed a rebound in the replay when the animals entered recovery sleep, but its magnitude remained much lower compared to the levels seen during natural sleep. Overall, our findings provide a systems-level understanding of why sleep benefits, but sleep loss impairs, hippocampal memory.